Faktor Faktor yang Berhubungan dengan Kejadian Hipertensi pada Lansia - Devi Natalia; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest / Calm, an increase in blood pressure that lasts for a long time can cause kidney damage, heart, and brain (stroke). World Health Organization (WHO) data shows that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world is diagnosed with hypertension. The number of people with hypertension continues to increase every year, it is estimated that in 2025 there will be 1.5 billion people affected by hypertension and it is estimated that every year 9.4 million people die from hypertension and its complications. The research Objective is To analyze the factors related to the incidence of hypertension in the elderly based on data through the literature review method Results: 6 research results were obtained according to the sample inclusion criteria of 64-137 respondents. The results showed 5 research journals there was a relationship between hypertension risk factors with a value of = 0.05 and one journal had no relationship between stress, physical activity, and smoking habits. 6 research journal articles using the literature review method there are 5 journals there is a relationship, namely stress, physical activity, and smoking habits and in 1 journal there is no relationship between stress, physical activity, and smoking habits in factors related to the incidence of hypertension in the elderly.